The Three Dimensions of Small Accommodation Businesses and Their Efficiency - Eleni Dimitriadou; Asimina Kouriati; Sofia Karampela; Anna Tafidou; Thomas Bournaris (Tourism and Hospitality, 2023)
Measuring efficiency and determining factors that may influence it are very important steps to improve the businesses’ competitive position, growth, and sustainability. This paper aims to investigate the efficiency of small accommodation businesses located in Greek non-coastal areas and to determine a set of factors that may affect it, from the perspective of the three dimensions of family businesses (family, business, ownership). The method adopted, in order for the research objective aim to be fulfilled, is the two-stage Data Envelopment Analysis model. In the first stage, the efficiency was estimated from a sample of 150 businesses. In the second stage, the influence of various factors on the examined efficiency was investigated by implementing a Bootstrap Truncated regression. The results showed that the majority of the examined businesses presented a low level of efficiency. Regarding the determination of the factors, it occurred that the manager’s age, ownership form, and business type influenced the relative efficiency level in contrast to the factors of the business’s age, the manager’s sex and education level, the state of succession, as well as the manager’s agricultural employment. By fulfilling the aim of this study, a significant contribution to the relative literature and especially to the hospitality field is offered.